2023
DOI: 10.3390/en16248042
|View full text |Cite
|
Sign up to set email alerts
|

The Modeling and Control of (Renewable) Energy Systems by Partial Differential Equations—An Overview

Verica Radisavljevic-Gajic,
Dimitri Karagiannis,
Zoran Gajic

Abstract: Mathematical models of energy systems have been mostly represented by either linear or nonlinear ordinary differential equations. This is consistent with lumped-parameter dynamic system modeling, where dynamics of system state variables can be fully described only in the time domain. However, when dynamic processes of energy systems display both temporal and spatial evolutions (as is the case of distributed-parameter systems), the use of partial differential equations is necessary. Distributed-parameter system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 188 publications
0
2
0
Order By: Relevance
“…In recent years, significant work has been carried out by numerous authors on the modeling and control of distributed-parameter energy systems governed by partial differential equations (PDEs), as has been reviewed in a recent paper by the authors [108]. Observers are often a necessary component of control systems when feedback information about system states cannot be directly measured.…”
Section: Distributed-parameter Observers For Energy Systems and Proce...mentioning
confidence: 99%
“…In recent years, significant work has been carried out by numerous authors on the modeling and control of distributed-parameter energy systems governed by partial differential equations (PDEs), as has been reviewed in a recent paper by the authors [108]. Observers are often a necessary component of control systems when feedback information about system states cannot be directly measured.…”
Section: Distributed-parameter Observers For Energy Systems and Proce...mentioning
confidence: 99%
“…Advanced modeling has demonstrated that hybrid wind-solar systems possess significant capabilities to balance the inherent variability of each renewable energy source. By employing geospatial optimization and intelligent operational strategies, these multitechnology systems can achieve enhanced capacity factors and improved reliability [4]. Yet, fully harnessing the capabilities of such systems poses considerable challenges.…”
Section: Introductionmentioning
confidence: 99%